Intensive Care Unit Delirium, Clinical Observations, and Patients' Statements: A Case Study. Issue 4 (July 2020) - Granberg-Axèll, Anetth; Bergbom, Ingegerd
Abstract : Background: In clinical practice, nurses use their clinical gaze and make observations in order to assess patients' medical conditions and care needs. However, signs of developing intensive care unit delirium (ICUD) are often difficult to determine, as communication with patients is usually limited because of intubation and the seriousness of their medical condition(s). Usually, ICUD is screened and diagnosed with different, mainly nonverbal instruments, which presupposes that the observer is skilled and experienced in recognizing symptoms and signs of delirium. Objectives: The objectives were to investigate if there was a concordance between data from continuous clinical observations described in the researcher's logbook and patients' statements of their experiences of delirium during their ICU stay. Methods: Inclusion criteria were that the patients had been mechanically ventilated and had stayed in the ICU for a minimum of 36 hours. From this, a multiple-case design (n = 19), based on 1 to 3 hours of observations in the ICU and 2 interviews, was used. The first interview was conducted at the hospital approximately 6 to 14 days after discharge from the ICU, and the second, 4 to 8 weeks following the first interview in patients' homes. Two typical cases were identified and described by a cross-case procedure. Results: A concordance between observations and patients' statements was found. Subtle, as well as obvious, signs of delirium were possible to detect by attentive observations over time and listening to what patients were trying to convey with their speech and body language. Experiencing delirium seemed to indicate existential suffering where the abnormal became the normal and not being able to distinguish between reality and fantasies. Conclusion: A continuity of skilled observations and listening to patients' statements are vital for detection of ongoing ICU delirium or experiences of delirium.